Fear of Being Laughed at in Children and Adolescents: Exploring the Importance of Overweight, Underweight, and Teasing - Kohlmann, Carl-Walter; Eschenbeck, Heike; Heim-Dreger, Uwe; Hock, Michael; Platt, Tracey; Ruch, Willibald (Frontiers in Psychology, 2018)
Weight bias toward obese youths is often accompanied by the experience of psychological stress in those affected. Therefore, the fear of being laughed at (i.e., gelotophobia) in overweight children and adolescents can be rather serious. In four studies, the importance of relative weight, self-awareness of weight (incl. satisfaction with weight), experiences of teasing and ridicule, as well as the role of social-evaluative situations in school were analyzed with regard to gelotophobia. In two online interviews of adults with pronounced gelotophobia (Study I: 102 English-speaking participants, Study II: 22 German-speaking participants) relating to reasons they assumed for their development of gelotophobia, there was evidence of injurious appearance-related experiences during childhood and adolescence. Study III (75 Swiss adolescents) was used to analyze associations between the experience of weight-related teasing and mockery with overweight, self-perceptions of weight, and gelotophobia. Especially in girls, overweight was associated with the experience of weight-related teasing and ridicule, which in turn was accompanied by gelotophobia. Study IV included 178 German adolescents who were asked to report their body image ("Do you think you are ... too thin, just the right weight, or too fat?"). In addition, gelotophobia, teasing, BMI based on self-reports, and joy at school were measured. In particular, girls who felt too fat and boys who felt too thin reported teasing. Teasing was related to diminished joy at school and to gelotophobia. Among boys, underweight mediated by weight-related teasing contributed to gelotophobia. The results suggest that more research should be devoted to gelotophobia and the experience of weight-related teasing and mocking to better understand factors contributing the well-being of children and adolescents with weight problems.